Seasonal analysis of the number of aeropiles in Anocentor nitens (Neumann, 1897) (Acari: Ixodidae) from the State of Rio de Janeiro, Brazil - Gilberto Salles Gazêta; Luciana Guerim; Marinete Amorim; Nicolau Maués Serra-Freire (Memorias do Instituto Oswaldo Cruz, 2001)
Variation between aeropile numbers of the right and left peritrematic plate in male and female Anocentor nitens (Neumann, 1897) is reported from a site in Brazil. From January to December 1998, 146 males and 247 females of A. nitens were recovered from Equus caballus L. in Silva Jardim District, State of Rio de Janeiro. Asymmetry of numbers of aeropiles between right and left plates occurred in 83.6% of the males and 82.2% of the females. Differences in the number of aeropiles between the sexes were not significant. Quantitative variation of aeropiles was correlated to the period of recovery, with significant asymmetry detected in August-September and November-December, mainly in males. Results suggest an adaptation, especially in the male ticks, that expresses itself as greater variation in the number of aeropiles in some periods of the year.